Making legal history : approaches and methodologies - Musson, Anthony, 1966-; Stebbings, Chantal (Cambridge : Cambridge University Press, 2012)
'Drawing together leading legal historians from a range of jurisdictions and cultures, this collection of essays addresses the fundamental methodological underpinning of legal history research. Via a broad chronological span and a wide range of topics, the contributors explore the approaches, methods and sources that together formthe basis of their research and shed light on the complexities of researching into the history of the law. By exploring the challenges posed by visual, unwritten and quasi-legal sources, the difficulties posed by traditional archival material and the novelty of exploring the development of legal culture and comparative perspectives, the book reveals the richness and dynamism of legal history research'--
Reflections on'doing' legal history / Sir John Baker -- Editing law reports and doing legal history : compatible or incompatible projects? / Paul Brand -- The indispensability of manuscript case notes to eighteenth-century barristers and judges / James Oldham -- Judging judges : the reputations of nineteenth-century judges and their sources / Patrick Polden -- Benefits and barriers : the making of Victorian legal history / Chantal Stebbings -- Methodology in legal history : from the history of free speech to the role of history in transatlantic legal thought / David M. Rabban -- The methodological debates in German-speaking Europe (1960-1990) / Marcel Senn -- Exploring the law in medieval minds : the duty of the legal historian to write the books of non-written law / Dirk Heirbaut -- Comparative legal history : a methodology / David Ibbetson -- 'They put to the torture all the ancient monuments' : reflections on making eighteenth-century Irish legal history / Sean Patrick Donlan -- The politics of historiography and the taxonomies of the colonial past : law, history and the tribes / Paul McHugh -- Lay legal history / Wilfrid Prest -- Antiquarianism and legal history / Michael Stuckey -- Re-examining King John and Magna Carta : reflections on reasons, methodology and methods / Jane Frecknall-Hughes -- Visual sources : mirror of justice or'through a glass darkly'? / Anthony Musson -- Sanctity, superstition and the death of Sarah Jacob / Richard W. Ireland.
Includes bibliographical references and index.
Keywords: Law -- Historiography